Lithium-ion secondary battery, method for manufacturing the same, and electric device
Patent Information
- Application Number
- CN202510475291.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-15
- Publication Date
- 2026-10-23
AI Technical Summary
[0033]下面将结合附图,对本申请实施例中的技术方案进行描述。
Smart Images

Figure CN122968375A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and more specifically, to a lithium-ion secondary battery and its preparation method and power application device. Background Technology
[0002] With increasing environmental pollution, the new energy industry is attracting more and more attention. Within the new energy industry, battery technology is a crucial factor in its development.
[0003] The development of battery technology requires consideration of various design factors, such as energy density, cycle life, storage performance, charge / discharge rate, and reliability. Among these, the design of the positive electrode is crucial to the performance of lithium-ion rechargeable batteries, directly affecting their storage and cycle performance. Therefore, improving the storage and cycle performance of lithium-ion rechargeable batteries is a pressing technical problem that needs to be solved. Summary of the Invention
[0004] This application is made in view of the above-mentioned issues, and its purpose is to provide a lithium-ion secondary battery and its preparation method and power device, which can improve the storage performance and cycle performance of the lithium-ion secondary battery.
[0005] In a first aspect, a lithium-ion secondary battery is provided, including a positive electrode sheet, the positive electrode sheet comprising a positive electrode active material and carbon nanotubes; at least a portion of the surface of the positive electrode active material is provided with a coating layer, the coating layer comprising graphene and carbon black.
[0006] In this embodiment, by providing a coating layer to cover at least a portion of the surface of the positive electrode active material, the direct contact between the positive electrode active material and the electrolyte is reduced, which helps to reduce side reactions between the positive electrode active material and the electrolyte, reduce lithium-ion consumption, and improve the storage performance of the lithium-ion secondary battery. By providing a coating layer including graphene and carbon black, on the one hand, graphene and carbon black are conductive, and by covering at least a portion of the surface of the positive electrode active material, the conductivity of the positive electrode active material can be improved, the internal resistance of the lithium-ion secondary battery can be reduced, and the cycle performance of the lithium-ion secondary battery can be improved. On the other hand, during the charging and discharging process of the lithium-ion secondary battery, the positive electrode sheet undergoes volume change. By placing carbon black particles in the coating layer, they contact and overlap with the carbon nanotubes in the positive electrode sheet, forming contact points in the conductive network, so that the carbon black particles and carbon nanotubes can be interconnected and conduct electricity. Graphene sheets are contacted and connected with carbon black particles and carbon nanotubes to form a conductive network, allowing electrons to flow smoothly and forming a continuous conductive path. This enables stable electron transfer during the charging and discharging process of the lithium-ion secondary battery, reducing its internal resistance and improving its cycle performance. Furthermore, by coating at least a portion of the surface of the positive electrode active material with graphene and carbon black, the contact area between the carbon black and graphene and the positive electrode active material is increased, improving the conductivity of the positive electrode active material. This reduces the need to increase the conductivity of the positive electrode active material by adding more conductive agents, thus reducing the amount of conductive agent used in the positive electrode sheet. It also increases the mass ratio of the positive electrode active material and binder, increasing the bonding strength between the binder and the positive electrode active material, and reducing the risk of the positive electrode active material detaching from the current collector. Therefore, this application's embodiment of the technical solution can improve the storage and cycle performance of lithium-ion secondary batteries.
[0007] In one possible implementation, the graphene coats at least a portion of the surface of the positive electrode active material, and the carbon black is disposed between the layers of the graphene.
[0008] In the above technical solution, graphene has good conductivity. When the positive electrode sheet undergoes volume expansion, by coating at least part of the surface of the positive electrode active material with graphene, the contact stability between graphene and the positive electrode active material is improved, which is beneficial to improving the conductivity of the positive electrode active material, reducing the internal resistance of the lithium-ion secondary battery, and improving the cycle performance of the lithium-ion secondary battery. In addition, the heteroatomic groups at the edge of graphene can improve the dispersion performance of graphene and positive electrode active material, which is beneficial to the processing and preparation of the positive electrode sheet. By setting carbon black in the interlayer of graphene, the carbon black particles play a supporting role in the layered structure of graphene, expanding the interlayer spacing of graphene, reducing the interlayer stacking phenomenon and particle aggregation phenomenon of graphene, improving the dispersion performance of graphene, further improving the stability of the conductive network between graphene, carbon black and carbon nanotubes, reducing the internal resistance of the lithium-ion secondary battery, and improving the storage performance and cycle performance of the lithium-ion secondary battery.
[0009] In one possible implementation, the mass ratio of the graphene to the carbon black satisfies 1:4 to 1:15.
[0010] In the above technical solutions, setting the mass ratio of graphene to carbon black within the aforementioned range is beneficial for improving the stability of the coating layer, enhancing the conductivity of the positive electrode active material, reducing the internal resistance of the lithium-ion secondary battery, and improving the storage and cycle performance of the lithium-ion secondary battery. When the mass ratio of graphene to carbon black is greater than or equal to 1:4, the mass proportion of carbon black in the coating layer is relatively high, and there are more carbon black particles filling the graphene interlayer structure. This helps reduce the stacking and agglomeration of graphene, and the carbon black particles form more conductive pathways with different graphene sheets and carbon nanotubes, which helps reduce the internal resistance of the lithium-ion secondary battery and improve its storage and cycle performance. When the mass ratio of graphene to carbon black is less than or equal to 1:15, the carbon black has a suitable mass proportion, which is beneficial for the uniform dispersion of carbon black particles in the graphene interlayer. This reduces the situation where a high carbon black content leads to a reduced mass proportion of the positive electrode active material and uneven distribution of it in the coating layer, thus reducing the storage and cycle performance of the lithium-ion secondary battery.
[0011] In one possible implementation, the volumetric particle size distribution Dv50 of the graphene satisfies: 5μm ≤ Dv50 ≤ 15μm. In the above technical solution, the graphene has a suitable particle size distribution, which is beneficial for improving the stability of the conductive network in the positive electrode, reducing the internal resistance of the lithium-ion secondary battery, and improving the storage performance and cycle performance of the lithium-ion secondary battery. When the volumetric particle size distribution (Dv50) of graphene is greater than or equal to 5 μm, the larger particle size of graphene is beneficial for its uniform coating on the surface of the positive electrode active material. This reduces the risk of coating layer detachment due to volume expansion or contraction of the positive electrode sheet during charging and discharging, and improves the contact stability between graphene and the positive electrode active material. The larger particle size of multilayered graphene sheets results in better coating of the positive electrode active material, thereby reducing the contact area between the positive electrode active material and the electrolyte, reducing lithium-ion consumption, and thus improving the storage and cycle performance of lithium-ion secondary batteries. When the volumetric particle size distribution (Dv50) of graphene is less than or equal to 15 μm, the larger specific surface area and better dispersion properties of graphene help reduce the aggregation of graphene particles, allowing graphene to uniformly coat the surface of the positive electrode active material and form a stable conductive network with carbon black and carbon nanotubes. This reduces the internal resistance of the lithium-ion secondary battery and improves its storage and cycle performance.
[0012] In one possible implementation, the carbon nanotubes include at least one of multi-walled carbon nanotubes, few-walled carbon nanotubes, and single-walled carbon nanotubes. This allows for the selection of different carbon nanotubes based on actual application requirements. For example, multi-walled carbon nanotubes have a larger diameter and better dispersion in the cathode slurry, which is beneficial for the uniform distribution of multi-walled carbon nanotubes in the cathode electrode and the fabrication of lithium-ion secondary batteries. Few-walled carbon nanotubes have fewer layers and a larger specific surface area, which is beneficial for increasing the contact area with carbon black and graphene, improving the conductivity of the cathode active material, and reducing the internal resistance of the lithium-ion secondary battery. Single-walled carbon nanotubes have a higher aspect ratio and a larger specific surface area, which is beneficial for increasing the contact area with carbon black and graphene, forming a stable conductive network, and improving the storage and cycle performance of the lithium-ion secondary battery.
[0013] In one possible implementation, based on the total mass of the positive electrode active material, the amount A of carbon nanotubes added satisfies: 1 wt.% ≤ A ≤ 3 wt.%.
[0014] In the above technical solution, by setting the amount of carbon nanotubes added within the aforementioned range, the fibrous carbon nanotubes can interlock with carbon black and graphene to form a stable conductive network, improving the conductivity of the positive electrode active material, reducing the internal resistance of the lithium-ion secondary battery, and enhancing the storage and cycle performance of the lithium-ion secondary battery. When the amount of carbon nanotubes added is greater than or equal to 1 wt.%, the positive electrode sheet contains sufficient carbon nanotubes, which is beneficial for forming a continuous conductive network and improving the conductivity of the positive electrode active material. Conversely, when the amount of carbon nanotubes added is less than or equal to 3 wt.%, the reduced amount significantly decreases the mass ratio of the positive electrode active material, thereby reducing the storage performance of the lithium-ion secondary battery.
[0015] In one possible implementation, the positive electrode active material comprises lithium nickel oxide, the chemical formula of which satisfies: Li 1+a [Ni x Co y Mn z M b O 2-c M includes at least one of Zr, Al, Ti, Sb, Nb, Te, Mg, B, Ca, V, Ta, or Sr, where 0.2 ≥ a ≥ -0.2, 1 > x ≥ 0.7, 0.3 > y > 0, 0.3 > z > 0, 0.3 > b ≥ 0, and 0.5 ≥ c ≥ 0. The high Ni content in the above-mentioned positive electrode active material is beneficial for obtaining high-energy-density lithium-ion secondary batteries.
[0016] Secondly, a method for preparing a lithium-ion secondary battery is provided, comprising: adding graphene to anhydrous ethanol and dispersing it to obtain a graphene dispersion; adding carbon black to the graphene dispersion and dispersing it to obtain a carbon black-graphene dispersion; spray-drying the carbon black-graphene dispersion to prepare a coating powder; mixing a positive electrode active material and the coating powder and ball-milling them to obtain an intermediate; calcining the intermediate at high temperature to obtain a positive electrode active material with a coating layer; preparing a positive electrode slurry using the positive electrode active material; coating the positive electrode slurry onto at least one side of a positive electrode current collector to prepare a positive electrode sheet; assembling the positive electrode sheet, negative electrode sheet, and separator into an electrode assembly; encapsulating the electrode assembly in an outer packaging; injecting electrolyte and encapsulating to obtain a lithium-ion secondary battery.
[0017] In the preparation method of the lithium-ion secondary battery in this application embodiment, dispersing graphene facilitates uniform dispersion of graphene and reduces graphene agglomeration. Adding carbon black to graphene for dispersion helps to place carbon black in the interlayer structure of graphene, expanding the interlayer spacing of graphene, further reducing graphene stacking and agglomeration, thereby improving the conductivity of graphene and the contact area with the positive electrode active material. Spray drying can quickly convert the dispersion into a uniform powder, reducing the segregation of graphene and carbon black. Mixing the positive electrode active material and the coating layer powder and ball milling it helps to uniformly coat the surface of the positive electrode active material under the mechanical force of the ball milling process, increasing the contact area between the coating layer and the positive electrode active material. By coating at least a portion of the surface of the positive electrode active material with a coating layer, the direct contact between the positive electrode active material and the electrolyte is reduced, which helps to reduce side reactions between the positive electrode active material and the electrolyte, reduce lithium-ion consumption, and improve the storage performance of the lithium-ion secondary battery. By incorporating graphene and carbon black into the coating layer, on the one hand, graphene and carbon black are conductive; coating at least a portion of the surface of the positive electrode active material can improve the conductivity of the positive electrode active material, reduce the internal resistance of the lithium-ion secondary battery, and improve the cycle performance of the lithium-ion secondary battery. On the other hand, during the charging and discharging process of the lithium-ion secondary battery, the positive electrode sheet undergoes volume changes. By placing carbon black particles in the coating layer, the carbon black particles can stably overlap with the carbon nanotubes in the positive electrode sheet, thus preventing different... The graphene sheets and carbon nanotubes are connected to form a continuous conductive path, thereby creating a stable conductive network, reducing the internal resistance of the lithium-ion secondary battery, and improving its cycle performance. Furthermore, by coating at least a portion of the surface of the positive electrode active material with graphene and carbon black, the contact area between the carbon black and graphene and the positive electrode active material is increased, improving the conductivity of the positive electrode active material. This reduces the need to increase the conductivity of the positive electrode active material by increasing the amount of conductive agent added, which helps to reduce the amount of conductive agent used in the positive electrode sheet, increase the mass ratio of the positive electrode active material and binder, increase the bonding strength between the binder and the positive electrode active material, and reduce the risk of the positive electrode active material detaching from the current collector. This, in turn, helps to improve the storage performance and cycle performance of the lithium-ion secondary battery.
[0018] In one possible implementation, the dispersion process includes at least one of high-speed shearing, ultrasonic treatment, and high-pressure homogenization. The dispersion process can reduce particle agglomeration, allowing graphene to be uniformly distributed in the solvent, thereby forming a uniform coating powder. This coating uniformly covers at least a portion of the surface of the positive electrode active material, improving the conductivity of the positive electrode active material.
[0019] In one possible implementation, the pressure P of the high-pressure homogenization process satisfies: 1500psi ≤ P ≤ 2500psi.
[0020] In the above technical solution, high-pressure homogenization forces the suspension through a small-aperture homogenizing valve under high pressure, generating significant shear and impact forces. This disperses and refines the particles, facilitating the placement of carbon black within the graphene interlayer structure. The pressure during high-pressure homogenization, within the aforementioned range, promotes uniform particle distribution in the solution, improving dispersion while minimizing the risk of excessive shear pressure damaging the graphene interlayer structure. When the pressure exceeds 1500 psi, the shear force is sufficient to break up carbon black agglomerates, promoting their embedding within the graphene layers. Conversely, when the pressure is below 2500 psi, excessive shear force is minimized, reducing the risk of over-exfoliation of graphene or damage to its interlayer structure, which could decrease the structural stability of the graphene.
[0021] In one possible implementation, the mass ratio of the positive electrode active material to the powder satisfies 100:(1:1.2). Mixing the positive electrode active material and the powder according to the above mass ratio is beneficial for the coating layer to uniformly coat at least a portion of the surface of the positive electrode active material.
[0022] Thirdly, an electrical device is provided, comprising a lithium-ion secondary battery according to the first aspect and any possible implementation thereof; and / or a lithium-ion secondary battery obtained according to the preparation method according to the second aspect and any possible implementation thereof, the lithium-ion secondary battery being used to provide electrical energy to the electrical device. Attached Figure Description
[0023] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the embodiments of this application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.
[0024] Figure 1 This is a schematic diagram of the structure of a single battery cell according to an embodiment of this application;
[0025] Figure 2 This is a schematic diagram of a method for preparing a lithium-ion secondary battery according to an embodiment of this application;
[0026] Figure 3 This is a schematic diagram of the structure of a battery device according to an embodiment of this application;
[0027] Figure 4 This is a schematic diagram of an electrical device according to an embodiment of this application;
[0028] Figure 5 This is a schematic diagram of an electrical device according to another embodiment of this application;
[0029] Figure 6 This is an XRD pattern of an embodiment of this application;
[0030] Figure 7 This is a schematic diagram of the volume particle size distribution of graphene according to an embodiment of this application;
[0031] Figure 8 This is a schematic diagram of the volumetric particle size distribution of the coating powder according to an embodiment of this application.
[0032] Reference numerals: 3: battery cell; 30: casing; 31: housing; 313: pressure relief mechanism; 32: end cap; 322: electrode terminal; 33: electrode assembly; 331: tab; 34: connecting member; 10: battery device; 11: housing; 111: first housing section; 112: second housing section; 1: vehicle; 4: controller; 5: motor; 2: energy storage device. Detailed Implementation
[0033] The technical solutions in the embodiments of this application will now be described with reference to the accompanying drawings.
[0034] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0035] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0036] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used in the description of this application is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms "comprising" and "having," and any variations thereof, in the description, claims, and accompanying drawings of this application are intended to cover non-exclusive inclusion. The terms "first," "second," etc., in the description, claims, or accompanying drawings of this application are used to distinguish different objects, not to describe a specific order or hierarchy.
[0037] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0038] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0039] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0040] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0041] Unless otherwise specified, the following terms have the following meanings. Any undefined terms have their technically accepted meanings.
[0042] In the embodiments of this application, the "intercalation" process refers to the process in which lithium ions are intercalated into the positive electrode active material and the negative electrode active material due to an electrochemical reaction, while the "extraction" and "deintercalation" processes mentioned in this application refer to the process in which lithium ions are extracted from the positive electrode active material and the negative electrode active material due to an electrochemical reaction.
[0043] In this application, the reference to "embodiment" means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a mutually exclusive, independent, or alternative embodiment. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described in this application can be combined with other embodiments.
[0044] Typically, a lithium-ion secondary battery includes a positive electrode, a negative electrode, an electrolyte, and a separator. During the charging and discharging process, active ions shuttle between the positive and negative electrodes, inserting and extracting. The electrolyte acts as a conductor between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, primarily prevents short circuits while allowing active ions to pass through. During charging, lithium ions are extracted from the positive electrode active material, move, and insert into the negative electrode active material; conversely, during discharging, lithium ions are extracted from the negative electrode active material, move, and insert into the positive electrode active material.
[0045] The development of battery technology must consider multiple design factors simultaneously, such as energy density, cycle life, capacity retention, charge / discharge rate, and reliability. Among these, the design of the positive electrode is crucial to the performance of lithium-ion rechargeable batteries, directly affecting their storage and cycle performance.
[0046] In lithium-ion secondary batteries, the conductivity of the positive electrode active material can be improved by adding carbon black and carbon nanotubes. Carbon black particles have a certain degree of conductivity and can connect with carbon nanotubes in the positive electrode sheet to form a conductive network, thereby improving the conductivity of the positive electrode active material. However, during the charging and discharging process of a lithium-ion secondary battery, the positive electrode sheet undergoes volume expansion or contraction, and the connection between carbon black and carbon nanotubes is prone to failure, leading to an increase in the internal resistance of the lithium-ion secondary battery and a decrease in its cycle performance. In some processing methods, increasing the amount of carbon black and carbon nanotubes added improves the conductivity of the positive electrode active material, but this reduces the mass ratio of the positive electrode active material and decreases the storage performance of the lithium-ion secondary battery. In other processing methods, graphene, carbon black, and carbon nanotubes are mixed with the positive electrode active material to prepare the lithium-ion secondary battery. Graphene has high conductivity, and the connection between graphene and carbon nanotubes through contact with carbon black particles forms a conductive network, improving the conductivity of the positive electrode active material and enhancing the cycle performance of the lithium-ion secondary battery. Due to the high surface energy and van der Waals forces between graphene layers, the graphene layers easily attract each other, leading to stacking and agglomeration of graphene particles. This reduces the contact area between graphene and the positive electrode active material, decreasing the graphene's conductivity. During the volume expansion or contraction of the positive electrode sheet, the connections between carbon black particles on the surface of the positive electrode active material and graphene / carbon nanotubes in the interparticle gaps are prone to failure, resulting in increased internal resistance and reduced cycle performance of the lithium-ion secondary battery.
[0047] In view of this, embodiments of this application provide a lithium-ion secondary battery, including a positive electrode sheet, the positive electrode sheet including a positive electrode active material, a coating layer and carbon nanotubes; the coating layer covers at least a portion of the surface of the positive electrode active material, and the coating layer includes graphene and carbon black.
[0048] In this embodiment, by providing a coating layer to cover at least a portion of the surface of the positive electrode active material, the direct contact between the positive electrode active material and the electrolyte is reduced, which helps to reduce side reactions between the positive electrode active material and the electrolyte, reduce lithium-ion consumption, and improve the storage performance of the lithium-ion secondary battery. By providing a coating layer including graphene and carbon black, on the one hand, graphene and carbon black are conductive, and by covering at least a portion of the surface of the positive electrode active material, the conductivity of the positive electrode active material can be improved, the internal resistance of the lithium-ion secondary battery can be reduced, and the cycle performance of the lithium-ion secondary battery can be improved. On the other hand, during the charging and discharging process of the lithium-ion secondary battery, the positive electrode sheet undergoes volume change. By placing carbon black particles in the coating layer, they contact and overlap with the carbon nanotubes in the positive electrode sheet, forming contact points in the conductive network, so that the carbon black particles and carbon nanotubes can be interconnected and conduct electricity. Graphene sheets are contacted and connected with carbon black particles and carbon nanotubes to form a conductive network, allowing electrons to flow smoothly and forming a continuous conductive path. This enables stable electron transfer during the charging and discharging process of the lithium-ion secondary battery, reducing its internal resistance and improving its cycle performance. Furthermore, by coating at least a portion of the surface of the positive electrode active material with graphene and carbon black, the contact area between the carbon black and graphene and the positive electrode active material is increased, improving the conductivity of the positive electrode active material. This reduces the need to increase the conductivity of the positive electrode active material by adding more conductive agents, thus reducing the amount of conductive agent used in the positive electrode sheet. It also increases the mass ratio of the positive electrode active material and binder, increasing the bonding strength between the binder and the positive electrode active material, and reducing the risk of the positive electrode active material detaching from the current collector. Therefore, this application's embodiment of the technical solution can improve the storage and cycle performance of lithium-ion secondary batteries.
[0049] It should be understood that the lithium-ion secondary battery in this application can be a battery pack or a single battery cell. Typically, a single battery cell includes a positive electrode, a negative electrode, an electrolyte, and a separator. The following section describes the lithium-ion secondary battery provided in this application and its various components.
[0050] [Lithium-ion rechargeable battery]
[0051] This application provides a lithium-ion secondary battery, including a positive electrode sheet, which includes a positive electrode active material and carbon nanotubes; at least a portion of the surface of the positive electrode active material is provided with a coating layer, which includes graphene and carbon black.
[0052] In this embodiment, by providing a coating layer to cover at least a portion of the surface of the positive electrode active material, the direct contact between the positive electrode active material and the electrolyte is reduced, which helps to reduce side reactions between the positive electrode active material and the electrolyte, reduce lithium-ion consumption, and improve the storage performance of the lithium-ion secondary battery. By providing a coating layer including graphene and carbon black, on the one hand, graphene and carbon black are conductive, and by covering at least a portion of the surface of the positive electrode active material, the conductivity of the positive electrode active material can be improved, the internal resistance of the lithium-ion secondary battery can be reduced, and the cycle performance of the lithium-ion secondary battery can be improved. On the other hand, during the charging and discharging process of the lithium-ion secondary battery, the positive electrode sheet undergoes volume change. By placing carbon black particles in the coating layer, they contact and overlap with the carbon nanotubes in the positive electrode sheet, forming contact points in the conductive network, so that the carbon black particles and carbon nanotubes can be interconnected and conduct electricity. Graphene sheets are contacted and connected with carbon black particles and carbon nanotubes to form a conductive network, allowing electrons to flow smoothly and forming a continuous conductive path. This enables stable electron transfer during the charging and discharging process of the lithium-ion secondary battery, reducing its internal resistance and improving its cycle performance. Furthermore, by coating at least a portion of the surface of the positive electrode active material with graphene and carbon black, the contact area between the carbon black and graphene and the positive electrode active material is increased, improving the conductivity of the positive electrode active material. This reduces the need to increase the conductivity of the positive electrode active material by adding more conductive agents, thus reducing the amount of conductive agent used in the positive electrode sheet. It also increases the mass ratio of the positive electrode active material and binder, increasing the bonding strength between the binder and the positive electrode active material, and reducing the risk of the positive electrode active material detaching from the current collector. Therefore, this application's embodiment of the technical solution can improve the storage and cycle performance of lithium-ion secondary batteries.
[0053] In this embodiment, graphene can be formed by two or more layers of graphene tightly stacked together through the interaction of van der Waals forces.
[0054] In some embodiments, graphene coats at least a portion of the surface of the positive electrode active material, and carbon black is disposed in the interlayer structure of the graphene.
[0055] It should be understood that the testing method for the particle distribution of the coating layer in this application embodiment is not limited, and any testing method known in the art can be used. As an example, the particle distribution of the coating layer can be observed by X-ray diffraction (XRD). Specifically, in the XRD diffraction pattern, the X-ray diffraction pattern of the coating layer has a diffraction peak A at a diffraction angle of approximately 26.5°, corresponding to the diffraction peak of graphene in the coating layer. Carbon black is placed in the interlayer structure of graphene. When carbon black is intercalated into graphene, the disorder increases, the interlayer spacing of graphene increases, and the interlayer stacking of graphene is reduced, thus reducing the intensity of diffraction peak A of the coating layer. The fact that diffraction peak A satisfies the above conditions indicates that the carbon black particles are set in the interlayer structure of graphene, which is beneficial to reducing the interlayer stacking and particle agglomeration of graphene, improving the dispersion performance of graphene, further improving the stability of the conductive network between graphene, carbon black and carbon nanotubes, reducing the internal resistance of lithium-ion secondary batteries, and improving the storage performance and cycle performance of lithium-ion secondary batteries.
[0056] In this embodiment, graphene exhibits good conductivity. When the positive electrode sheet undergoes volume expansion, by coating at least a portion of the surface of the positive electrode active material with graphene, the contact stability between graphene and the positive electrode active material is improved, which is beneficial for enhancing the conductivity of the positive electrode active material, reducing the internal resistance of the lithium-ion secondary battery, and improving the cycle performance of the lithium-ion secondary battery. Furthermore, the heteroatomic groups at the edge of graphene can improve the dispersion performance of graphene and the positive electrode active material, which is beneficial for the processing and preparation of the positive electrode sheet. By placing carbon black between the layers of graphene, the carbon black particles play a supporting role in the layered structure of graphene, expanding the interlayer spacing of graphene, reducing the interlayer stacking phenomenon and particle agglomeration phenomenon of graphene, improving the dispersion performance of graphene, further enhancing the stability of the conductive network between graphene, carbon black, and carbon nanotubes, reducing the internal resistance of the lithium-ion secondary battery, and improving the storage performance and cycle performance of the lithium-ion secondary battery.
[0057] In some embodiments, the mass ratio of graphene to carbon black is 1:4 to 1:15.
[0058] Specifically, the mass ratio of graphene to carbon black can be 1:4, 1:6, 1:8, 1:10, 1:12, 1:14, 1:15, or any value within the above two ranges.
[0059] In this embodiment, setting the mass ratio of graphene to carbon black to meet the above-mentioned range is beneficial to improving the stability of the coating layer, enhancing the conductivity of the positive electrode active material, reducing the internal resistance of the lithium-ion secondary battery, and improving the storage and cycle performance of the lithium-ion secondary battery. When the mass ratio of graphene to carbon black is greater than or equal to 1:4, the mass proportion of carbon black in the coating layer is relatively high, and there are more carbon black particles filling the graphene interlayer structure. This helps to reduce the stacking and agglomeration of graphene. The carbon black particles form more conductive pathways with different graphene sheets and carbon nanotubes, which helps to reduce the internal resistance of the lithium-ion secondary battery and improve its storage and cycle performance. When the mass ratio of graphene to carbon black is less than or equal to 1:15, the carbon black has a suitable mass proportion, which is beneficial to the uniform dispersion of carbon black particles in the graphene interlayer. This reduces the situation where a high carbon black content leads to a reduced mass proportion of the positive electrode active material and uneven distribution of it in the coating layer, thus reducing the storage and cycle performance of the lithium-ion secondary battery. In some embodiments, the volumetric particle size distribution Dv50 of graphene satisfies: 5μm≤Dv50≤15μm.
[0060] Dv50 can refer to the particle size at which the cumulative particle size distribution number of a sample reaches 50%, meaning that 50% of the particles are smaller than Dv50.
[0061] Specifically, the volumetric particle size distribution Dv50 of graphene can be 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm or any two of the above ranges.
[0062] In this embodiment, graphene has a suitable particle size distribution, which is beneficial to improving the stability of the conductive network in the positive electrode, reducing the internal resistance of the lithium-ion secondary battery, and improving the storage performance and cycle performance of the lithium-ion secondary battery. When the volumetric particle size distribution (Dv50) of graphene is greater than or equal to 5 μm, the larger particle size of graphene is beneficial for its uniform coating on the surface of the positive electrode active material. This reduces the risk of coating layer detachment due to volume expansion or contraction of the positive electrode sheet during charging and discharging, and improves the contact stability between graphene and the positive electrode active material. The larger particle size of multilayered graphene sheets results in better coating of the positive electrode active material, thereby reducing the contact area between the positive electrode active material and the electrolyte, reducing lithium-ion consumption, and thus improving the storage and cycle performance of lithium-ion secondary batteries. When the volumetric particle size distribution (Dv50) of graphene is less than or equal to 15 μm, the larger specific surface area and better dispersion properties of graphene help reduce the aggregation of graphene particles, allowing graphene to uniformly coat the surface of the positive electrode active material and form a stable conductive network with carbon black and carbon nanotubes. This reduces the internal resistance of the lithium-ion secondary battery and improves its storage and cycle performance.
[0063] In some embodiments, carbon nanotubes include at least one of multi-walled carbon nanotubes, few-walled carbon nanotubes, and single-walled carbon nanotubes. This allows for the selection of different carbon nanotubes based on actual application requirements. For example, multi-walled carbon nanotubes have a larger diameter and better dispersion in the cathode slurry, which is beneficial for the uniform distribution of multi-walled carbon nanotubes in the cathode electrode and the preparation of lithium-ion secondary batteries. Few-walled carbon nanotubes have fewer layers and a larger specific surface area, which is beneficial for increasing the contact area with carbon black and graphene, improving the conductivity of the cathode active material, and reducing the internal resistance of the lithium-ion secondary battery. Single-walled carbon nanotubes have a higher aspect ratio and a larger specific surface area, which is beneficial for increasing the contact area with carbon black and graphene, forming a stable conductive network, and improving the storage performance and cycle performance of the lithium-ion secondary battery.
[0064] In some embodiments, the diameter of few-walled carbon nanotubes can be 1 nm-5 nm, or the diameter of multi-walled carbon nanotubes can be 5 nm-50 nm. This can further improve the conductivity of the positive electrode active material.
[0065] Specifically, the diameter of the few-walled carbon nanotubes can be 1 nm, 2 nm, 3 nm, 4 nm, 5 nm or any value within the above range; the diameter of the multi-walled carbon nanotubes can be 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm or any value within the above range.
[0066] The diameter of a carbon nanotube refers to the average of its outer and inner diameters when the tube wall is relatively thin.
[0067] In some embodiments, based on the total mass of the positive electrode active material, the amount of carbon nanotubes added, A, satisfies the following condition: 1 wt.% ≤ A ≤ 3 wt.%.
[0068] The mass content of carbon nanotubes can be 1 wt.%, 1.25 wt.%, 1.5 wt.%, 1.75 wt.%, 2.0 wt.%, 2.25 wt.%, 2.5 wt.%, 2.75 wt.%, 3.0 wt.%, or any value within the above range.
[0069] In this embodiment, by setting the amount of carbon nanotubes added to meet the above-mentioned range, the fibrous carbon nanotubes can interlock with carbon black and graphene to form a stable conductive network, improving the conductivity of the positive electrode active material, reducing the internal resistance of the lithium-ion secondary battery, and improving the storage and cycle performance of the lithium-ion secondary battery. When the amount of carbon nanotubes added is greater than or equal to 1 wt.%, the positive electrode sheet has sufficient carbon nanotubes, which is beneficial for forming a continuous conductive network and improving the conductivity of the positive electrode active material. When the amount of carbon nanotubes added is less than or equal to 3 wt.%, the amount of carbon nanotubes added is significantly reduced, which reduces the mass ratio of the positive electrode active material and reduces the storage performance of the lithium-ion secondary battery.
[0070] [Positive electrode plate]
[0071] The positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector, the positive active material layer including a positive active material.
[0072] As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive active material layer is disposed on either or both of the two opposite surfaces of the positive current collector.
[0073] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0074] In some embodiments, the positive electrode active material in the positive electrode active material layer includes a lithium phosphate with an olivine structure. Examples of lithium phosphate with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP), lithium iron phosphate and carbon composites, lithium manganese phosphate (such as LiMnPO4), lithium manganese phosphate and carbon composites, lithium manganese iron phosphate, and lithium manganese iron phosphate and carbon composites.
[0075] The positive electrode active material layer may optionally include at least one of the positive electrode active materials known in the art for batteries: lithium transition metal oxides and their respective modified compounds. However, this application is not limited to these materials, and other conventional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxides (such as LiCoO2), lithium nickel oxides (such as LiNiO2), lithium manganese oxides (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, and lithium nickel cobalt manganese oxides (such as LiNi). 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also known as NCM) 333 LiNi 0.5 Co 0.2 Mn 0.3 O2 (also known as NCM) 523 LiNi 0.5 Co 0.25 Mn 0.25 O2 (also known as NCM) 211 LiNi 0.6 Co 0.2 Mn 0.2 O2 (also known as NCM) 622 LiNi 0.8 Co 0.1 Mn 0.1 O2 (also known as NCM) 811 ), lithium nickel cobalt aluminum oxide (such as LiNi) 0.85 Co 0.15 Al 0.05 At least one of O2 and its modified compounds.
[0076] In some embodiments, the positive electrode active material comprises lithium nickel oxide, the chemical formula of which satisfies: Li 1+a [Ni x Co y Mn z M b O 2-cM includes at least one of Zr, Al, Ti, Sb, Nb, Te, Mg, B, Ca, V, Ta or Sr, 0.2≥a≥-0.2, 1>x≥0.7, 0.3>y>0, 0.3>z>0, 0.3>b≥0, 0.5≥c≥0, and x+y+z+b=1.
[0077] a can be -0.2, -0.1, -0.04, 0, 0.04, 0.1, 0.2, or any value within the above ranges; x can be 0.7, 0.75, 0.8, 0.9, 0.95, 0.96, or any value within the above ranges; y can be 0.1, 0.2, or any value within the above ranges; z can be 0.1, 0.2, or any value within the above ranges; b can be 0, 0.1, 0.2, or any value within the above ranges; and c can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, or any value within the above ranges. As an example, b is 0, and the positive electrode active material includes LiNi. 0.8 Co 0.1 Mn 0.1 O2. As another example, b>0, positive electrode active materials include LiNi. 0.7 Co 0.1 Mn 0.1 Al 0.1 O2.
[0078] The positive electrode active material included in the above chemical formula can be called a high-nickel ternary material. Compared with ternary materials with low nickel content or materials such as lithium iron phosphate, high-nickel ternary materials have a higher specific capacity. Without changing the capacity ratio of the positive electrode active material, using high-nickel ternary materials is beneficial to improving the total mass of the positive electrode active material, which is beneficial to obtaining a high-energy-density lithium-ion secondary battery.
[0079] In some embodiments, the positive electrode active material layer includes a conductive agent. The conductive agent may be selected from one or more of carbon nanotubes, graphene, and carbon black in any of the possible embodiments or implementations described above.
[0080] In some embodiments, based on the total mass of the positive electrode active material layer, the total mass content of carbon black and graphene in the conductive agent satisfies: 2% to 5%.
[0081] The total mass content of carbon black and graphene can be 2%, 3%, 4%, 5%, or any value within the above range. This ensures sufficient carbon black and graphene in the positive electrode active material layer, which is beneficial for improving the storage and cycle performance of lithium-ion secondary batteries. When the total mass content of carbon black and graphene is greater than or equal to 2%, the contact area between carbon black and graphene and the positive electrode active material is larger, which is beneficial for improving the conductivity of the positive electrode active material. When the content of carbon black and graphene is less than or equal to 5%, it can reduce the excessive amount of conductive agent in the positive electrode sheet, lower the mass ratio of the positive electrode active material and binder, and reduce the risk of the positive electrode active material detaching from the current collector, thereby improving the storage and cycle performance of lithium-ion secondary batteries.
[0082] In some embodiments, the positive electrode active material layer may optionally include a binder. As an example, the binder may include at least one selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.
[0083] In some embodiments, the positive electrode sheet can be prepared by forming a positive electrode slurry using the components described above. For example, the positive electrode active material, conductive agent, binder, and any other components are dispersed in a solvent (e.g., N-methylpyrrolidone) to form the positive electrode slurry. The positive electrode slurry is then coated onto a positive electrode current collector, and after drying, cold pressing, and other processes, the positive electrode sheet is obtained.
[0084] [Negative electrode plate]
[0085] The negative electrode sheet includes a negative current collector and a negative active material layer disposed on the negative current collector, the negative active material layer including a negative active material. The negative active material layer can be disposed on one side surface of the negative current collector or on both sides of the negative current collector.
[0086] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0087] In some embodiments, the negative electrode active material may be a negative electrode active material known in the art for use in batteries. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0088] In some embodiments, the negative electrode active material layer may optionally include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0089] As described above, in some embodiments, the negative electrode active material layer may optionally include conductive carbon. The conductive carbon may be selected from at least one of superconducting carbon, acetylene black, conductive carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0090] In some embodiments, the negative electrode active material layer may also optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0091] In some embodiments, the negative electrode sheet can be prepared by dispersing the above-mentioned components for preparing the negative electrode sheet, such as negative electrode active material, conductive carbon, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto a negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.
[0092] [Electrolytes]
[0093] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific limitations on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, semi-solid, or fully solid.
[0094] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.
[0095] For lithium-ion battery cells or lithium metal battery cells, the electrolyte salt may include one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.
[0096] For lithium-ion battery cells or lithium metal battery cells, the solvent may include one or more of the following: ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.
[0097] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.
[0098] [Isolation membrane]
[0099] The separator is a membrane. This application does not have any particular restrictions on the type of separator. Any well-known porous separator with good chemical and mechanical stability can be selected.
[0100] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0101] Positive electrode, negative electrode and separator can be made into electrode assembly by winding process or stacking process.
[0102] [Battery cell]
[0103] In some embodiments, the lithium-ion secondary battery can be a single battery cell.
[0104] The embodiments of this application do not impose any particular restrictions on the shape of the battery cell; it can be cylindrical, square, or any other arbitrary shape. Figure 1 This is a schematic diagram of the structure of a battery cell according to an embodiment of this application. For example, as shown... Figure 1As shown, the battery cell 3 is a square battery cell. The battery cell 3 includes a housing 30 and an electrode assembly 33 disposed in the housing 30. The housing 30 includes a shell 31 and an end cap 32, which is used to cover the opening of the shell 31.
[0105] The electrode assembly 33 can be manufactured from a positive electrode, a negative electrode, and a separator through a winding process or a stacking process. The electrode assembly 33 may include an electrode assembly body and tabs 331 extending from the electrode assembly body.
[0106] End cap 32 includes electrode terminals 322, such as Figure 1 As shown, the end cap 32 includes two electrode terminals 322, one of which is a positive electrode terminal and the other is a negative electrode terminal.
[0107] The battery cell 3 also includes a connecting member 34 for connecting the tab 331 and the electrode terminal 322 of the electrode assembly 33. For example, one connecting member 34 is used to connect the tab of the positive electrode and the positive electrode terminal, and another connecting member 34 is used to connect the tab of the negative electrode and the negative electrode terminal.
[0108] In some embodiments, the battery cell 3 includes a pressure relief mechanism 313 for releasing substances inside the battery cell 3 when thermal runaway occurs, thereby reducing the risk caused by the failure to release the emissions from the battery cell 3 in a timely manner.
[0109] In some embodiments, individual battery cells can be assembled into a battery module. The number of individual battery cells contained in a battery module can be one or more, and the specific number can be selected by those skilled in the art based on the application and capacity of the battery module.
[0110] [Preparation methods for lithium-ion secondary batteries]
[0111] Figure 2 This is a schematic diagram of a method for preparing a lithium-ion secondary battery according to an embodiment of this application. Figure 2 As shown, the preparation method 200 of the lithium-ion secondary battery includes the following steps.
[0112] Step 210: Add graphene to anhydrous ethanol for dispersion treatment to obtain graphene dispersion.
[0113] Step 220: Add carbon black to the graphene dispersion and disperse it to obtain a carbon black-graphene dispersion.
[0114] Step 230: The carbon black-graphene dispersion is spray-dried to prepare powder.
[0115] Step 240: Mix the positive electrode active material and powder, and ball mill them to obtain an intermediate.
[0116] Step 250: The intermediate is subjected to high-temperature calcination to obtain a positive electrode active material with a coating layer.
[0117] Step 260: Prepare a positive electrode slurry using positive electrode active material and carbon nanotubes, and coat the positive electrode slurry onto at least one side of the positive electrode current collector to obtain a positive electrode sheet.
[0118] Step 270: Provide a positive electrode sheet, a negative electrode sheet, and a separator to assemble an electrode assembly, place the electrode assembly into an outer packaging for encapsulation, inject electrolyte, and then encapsulate to obtain a lithium-ion secondary battery.
[0119] In the preparation method of the lithium-ion secondary battery in this application embodiment, dispersing graphene is beneficial to the uniform dispersion of graphene and reduces graphene agglomeration; adding carbon black to graphene for dispersion further helps to reduce interlayer stacking and particle agglomeration of graphene; spray drying can quickly convert the dispersion into uniform powder, reducing the segregation of graphene and carbon black; mixing the positive electrode active material and powder and ball milling them, under the mechanical force of the ball milling process, helps to uniformly coat the surface of the positive electrode active material with powder, increasing the contact area between the coating layer and the positive electrode active material. By coating at least a portion of the surface of the positive electrode active material with a coating layer, the direct contact between the positive electrode active material and the electrolyte is reduced, which helps to reduce side reactions between the positive electrode active material and the electrolyte, reduce lithium-ion consumption, and improve the storage performance of the lithium-ion secondary battery. By incorporating graphene and carbon black into the coating layer, on the one hand, graphene and carbon black are conductive; coating at least a portion of the surface of the positive electrode active material can improve the conductivity of the positive electrode active material, reduce the internal resistance of the lithium-ion secondary battery, and improve the cycle performance of the lithium-ion secondary battery. On the other hand, during the charging and discharging process of the lithium-ion secondary battery, the positive electrode sheet undergoes volume changes. By placing carbon black particles in the coating layer, the carbon black particles can stably overlap with the carbon nanotubes in the positive electrode sheet, thus preventing different... The graphene sheets and carbon nanotubes are connected to form a continuous conductive path, thereby creating a stable conductive network, reducing the internal resistance of the lithium-ion secondary battery, and improving its cycle performance. Furthermore, by coating at least a portion of the surface of the positive electrode active material with graphene and carbon black, the contact area between the carbon black and graphene and the positive electrode active material is increased, improving the conductivity of the positive electrode active material. This reduces the need to increase the conductivity of the positive electrode active material by increasing the amount of conductive agent added, which is beneficial for reducing the amount of conductive agent used in the positive electrode sheet, increasing the mass ratio of the positive electrode active material and binder, increasing the bonding strength between the binder and the positive electrode active material, and reducing the risk of the positive electrode active material detaching from the current collector. Therefore, this application's embodiment of the technical solution can improve the storage performance and cycle performance of lithium-ion secondary batteries.
[0120] In some embodiments, the dispersion treatment includes at least one of high-speed shearing, ultrasonic treatment, and high-pressure homogenization. This dispersion treatment can reduce particle agglomeration, allowing graphene to be uniformly distributed in the solvent, thereby forming a uniform coating powder. This coating uniformly covers at least a portion of the surface of the positive electrode active material, improving the conductivity of the positive electrode active material. For example, the shear force during high-speed shearing helps overcome van der Waals forces between particles, resulting in uniform particle dispersion; the ultrasonic waves during ultrasonic treatment can reduce surface damage and particle agglomeration; high-pressure homogenization, by forcing the dispersion through tiny pores under high pressure, generates extremely high shear and impact forces, which facilitates collisions between carbon black particles and graphene, allowing them to enter the interlayer structure of graphene, reducing interlayer stacking and particle agglomeration, improving graphene dispersibility, and thus improving the uniformity of the coating powder.
[0121] In some embodiments, S210 includes adding graphene to anhydrous ethanol, performing ultrasonic treatment and high-pressure homogenization to obtain a graphene dispersion; S220 includes adding carbon black to the graphene dispersion, performing high-speed shearing, ultrasonic treatment and high-pressure homogenization to obtain a carbon black-graphene dispersion.
[0122] In some embodiments, the pressure P of the high-pressure homogenization process satisfies 1500psi≤P≤2500psi.
[0123] In this embodiment, high-pressure homogenization forces the suspension through a small-aperture homogenizing valve under high pressure, generating significant shear and impact forces. This disperses and refines the particles, facilitating the placement of carbon black within the graphene interlayer structure. The pressure during high-pressure homogenization falls within the aforementioned range, ensuring uniform particle distribution in the solution and improving dispersion while minimizing the risk of excessive shear pressure damaging the graphene interlayer structure. When the pressure exceeds 1500 psi, the shear force is sufficient to break up carbon black agglomerates, promoting their embedding within the graphene layers. Conversely, when the pressure is below 2500 psi, excessive shear force is minimized, reducing the risk of over-exfoliation of graphene or damage to its interlayer structure, which could decrease the structural stability of the graphene.
[0124] In some embodiments, the mass ratio of the positive electrode active material to the powder is 100:(1:1.2). Mixing the positive electrode active material and the powder according to the above mass ratio is beneficial to uniformly coat the coating layer on at least a portion of the surface of the positive electrode active material.
[0125] In some embodiments, the high-temperature calcination treatment temperature is 400–600°C, which is beneficial for obtaining a positive electrode active material with a coating layer.
[0126] In some embodiments, the adhesive includes at least one of asphalt, phenolic resin, furfural resin, and epoxy resin.
[0127] [Battery Device]
[0128] In some embodiments, the lithium-ion secondary battery is a battery device, which may include one or more battery cells.
[0129] Figure 3 This is a schematic diagram of the structure of a battery device according to an embodiment of this application. For example, such as... Figure 3 As shown, the battery device 10 is a battery pack. The battery pack may include a housing and multiple individual battery cells housed within the housing. These individual battery cells are connected in series, parallel, or a combination of both. The individual battery cells can directly assemble into a battery pack, or they can first be assembled into battery modules, and then multiple battery modules can be combined to form a battery pack.
[0130] The battery device 10 may further include a housing 11, which has a hollow interior and houses multiple battery cells 3. For example, multiple battery cells 3 may be connected in parallel, series, or a combination thereof and then placed inside the housing 11. The housing 11 may include a first housing portion 111 and a second housing portion 112, which are fitted together to form the housing 11. The shapes of the first housing portion 111 and the second housing portion 112 may be determined by the shape of the components housed within, for example, by the shape of the combination of multiple battery cells 3 housed within. At least one of the first housing portion 111 and the second housing portion 112 may have an opening. For example, as... Figure 3 As shown, the first housing portion 111 and the second housing portion 112 can both be hollow cuboids with one open side each. The openings of the first housing portion 111 and the second housing portion 112 are opposite to each other, and the first housing portion 111 and the second housing portion 112 are interlocked to form a housing 11 with a closed chamber, which can be used to accommodate multiple battery cells 3. The multiple battery cells 3 are connected in parallel, series, or mixed and placed inside the housing 11 formed by the interlocking of the first housing portion 111 and the second housing portion 112.
[0131] For example, unlike Figure 3 As shown, either the first housing portion 111 or the second housing portion 112 may have only one hollow cuboid with an opening, while the other is plate-shaped to cover the opening. Taking the second housing portion 112 as a hollow cuboid with one opening and the first housing portion 111 as a plate-shaped example, then the first housing portion 111 covers the opening of the second housing portion 112 to form a housing 11 with a closed chamber, which can be used to accommodate multiple battery cells 3.
[0132] In some embodiments, the battery device 10 may further include other components. For example, the battery device 10 may further include a busbar component, which can be used to realize electrical connections between multiple battery cells 3, such as in parallel, series, or mixed connections. Specifically, the busbar component can realize electrical connections between battery cells 3 by connecting to the electrode terminals of the battery cells 3; or, the busbar component can also realize electrical connections between battery cells 3 by connecting to other components of the battery cells 3. The busbar component can be fixed to corresponding components of the battery cells 3 by welding, for example, by welding to electrode terminals, sealing structures, or housings, etc., and the embodiments of this application are not limited thereto.
[0133] The battery cells 3 can be directly assembled into the battery device 10, or they can be first assembled into battery modules, and then multiple battery modules can be assembled into the battery device 10.
[0134] In some embodiments, the battery device 10 may be located in an energy storage device. The energy storage device includes an energy storage container, an energy storage cabinet, etc.
[0135] [Electrical appliances]
[0136] This includes at least one of the lithium-ion secondary batteries, battery modules, or battery packs provided in this application. The lithium-ion battery, battery module, or battery pack can be used as a power source for an electrical device or as an energy storage unit for that device. Electrical devices can include, but are not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0137] As an electrical device, lithium-ion secondary batteries, battery modules, or battery packs can be selected according to their usage requirements.
[0138] Electrical equipment can include vehicles, mobile phones, portable devices, laptops, ships, spacecraft, electric toys, and power tools, etc. Vehicles can be gasoline-powered cars, natural gas-powered cars, or new energy vehicles; new energy vehicles can be pure electric vehicles, hybrid electric vehicles, or range-extended electric vehicles, etc. Spacecraft include airplanes, rockets, space shuttles, and spacecraft, etc. Electric toys include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc. Power tools include metal cutting power tools, grinding power tools, assembly power tools, and railway power tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators, and electric planers, etc. This application does not impose any special limitations on the above-mentioned electrical equipment.
[0139] Figure 4This is a schematic diagram of an electrical device according to an embodiment of this application. Figure 4 As shown, this application provides an electrical device, which can be a vehicle 1, and includes the lithium-ion secondary battery in the above embodiment.
[0140] Vehicle 1 can be a gasoline-powered vehicle, a natural gas-powered vehicle, or a new energy vehicle. New energy vehicles can be pure electric vehicles, hybrid electric vehicles, or range-extended electric vehicles, etc. A motor 5, a controller 4, and a battery device 10 can be installed inside vehicle 1. The controller 4 controls the battery device 10 to supply power to the motor 5. For example, the battery device 10 can be installed under, at the front, or at the rear of vehicle 1. The battery device 10 can be used to power vehicle 1; for example, it can serve as the operating power source for the vehicle 1's electrical system, such as meeting the power requirements for starting, navigation, and operation. In another embodiment of this application, the battery device 10 can not only serve as the operating power source for vehicle 1 but also as the driving power source, replacing or partially replacing gasoline or natural gas to provide driving power to vehicle 1.
[0141] Another example device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a lithium-ion rechargeable battery as their power source.
[0142] Figure 5 This is a schematic diagram of an electrical device according to another embodiment of this application. Figure 5 As shown, this application provides an electrical device, which is an energy storage device 2, and the energy storage device 2 may include multiple battery devices 10. The energy storage device 2 can be applied to a power storage station to store and release electrical energy.
[0143] Alternatively, the electrical device may also be an energy storage device, a lighting device, a spacecraft, etc., as is the case in the embodiments of this application.
[0144] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0145] [Examples and Comparative Examples]
[0146] Example 1
[0147] (1) Preparation of coating powder
[0148] Graphene (10g) was added to 2L of anhydrous ethanol, ultrasonicated at 25℃ for 1h, and homogenized at 2000psi for 30min to obtain a graphene dispersion with a mass concentration of 5mg / mL. 80g of carbon black was added to the graphene dispersion, sheared at high speed for 30min, ultrasonicated for 2h, and homogenized at 2000psi for 1h to obtain a carbon black-graphene dispersion. The carbon black-graphene dispersion was spray-dried at 70℃ in a spray dryer to obtain a coating powder. The mass ratio of graphene to carbon black was 1:8.
[0149] (2) Preparation of positive electrode active material
[0150] LiNi, the positive electrode active material 0.8 Co 0.1 Mn 0.1 O2 and the above-mentioned coating powder are mixed at a mass ratio of 100:1, added to a ball mill jar, and ball-milled in a planetary ball mill at 100 r / min for 2 h to obtain an intermediate. The intermediate is placed in an alumina crucible and sintered in a muffle furnace at 200 °C for 30 min to obtain a positive electrode active material with a coating.
[0151] (3) Preparation of positive electrode sheet
[0152] LiNi with coating 0.8 Co 0.1 Mn 0.1 O2, single-walled carbon nanotubes, polyvinylidene fluoride (PVDF) binder, and N-methylpyrrolidone (NMP) solvent were mixed uniformly at a mass ratio of 98.5:0.5:1:21 and stirred thoroughly to prepare a positive electrode slurry. The positive electrode slurry was then uniformly coated onto two opposite surfaces of a positive electrode current collector aluminum foil, followed by drying, cold pressing, and slitting to obtain the positive electrode sheet. The single-walled carbon nanotubes had a length of 2 μm and a diameter of 1 nm.
[0153] (4) Preparation of negative electrode sheet
[0154] Artificial graphite, conductive carbon black (Super P), styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) were dissolved in deionized water at a mass ratio of 96.2:1:1:1.8. After thorough mixing, a negative electrode slurry was prepared. The negative electrode slurry was then coated onto a negative electrode current collector to obtain a negative electrode sheet with a negative electrode active material layer.
[0155] (5) Separating membrane
[0156] The separator is made of 13μm polyethylene (PE) film.
[0157] (6) Preparation of electrolyte
[0158] The electrolyte was prepared in an argon-atmospheric glove box with both water and oxygen content less than 0.1 ppm. The specific process was as follows: ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed uniformly at a volume ratio of 30:70. Then, 12.5 wt% of lithium hexafluorophosphate (LiPF6) was added, and the mixture was stirred thoroughly until completely dissolved. The lithium salt concentration was 1.0 mol / L.
[0159] (7) Preparation of secondary battery cells
[0160] The positive electrode, separator, and negative electrode are prepared in sequence, with the separator positioned between the positive and negative electrodes to provide isolation. The electrodes are then wound and hot-pressed to form an electrode assembly. The electrode assembly is then welded to the end cap, placed in a square aluminum shell, dried at 80°C, and injected with electrolyte. The assembly is then allowed to stand, hot-cold pressed, formed, shaped, and tested for capacity to finally obtain a single secondary battery cell.
[0161] Examples 2-4
[0162] Compared to Example 1, the mass ratio of graphene to carbon black is different. Specific parameters are detailed in Table 1.
[0163] Examples 5-6
[0164] The graphene particle size is different compared to Example 1. Specific parameters are detailed in Table 1.
[0165] Examples 7-8
[0166] Compared to Example 1, the types of carbon nanotubes are different. Specific parameters are detailed in Table 1. The few-walled carbon nanotubes have a length of 2 μm and a diameter of 5 nm; the multi-walled carbon nanotubes have a length of 2 μm and a diameter of 20 nm.
[0167] Examples 9-10
[0168] Compared to Example 1, the high-pressure homogenization process during the coating preparation is different. Specific parameters are detailed in Table 1.
[0169] Comparative Example 1
[0170] Compared to Example 1, no carbon black was added during the preparation of the coating layer. Specific parameters are detailed in Table 1.
[0171] Comparative Example 2
[0172] Compared to Example 1, carbon black, graphene, and carbon nanotubes were directly mixed with the positive electrode active material to prepare the positive electrode slurry, and no coating layer was formed on the surface of the positive electrode active material. Specific parameters are detailed in Table 1.
[0173] The specific parameters of the positive electrode in the embodiments and comparative examples are shown in Table 1.
[0174] Table 1. Specific parameters of the positive electrode sheets in the embodiments and comparative examples.
[0175]
[0176] Table 2 Test results of the examples and comparative examples
[0177]
[0178]
[0179] In Table 1, A represents the amount of carbon nanotubes added based on the total mass of the positive electrode active material. Dv50 represents the volumetric particle size distribution of graphene.
[0180] Examples 1-10 and Comparative Examples 1-2 and their test results are explained below:
[0181] Referring to Examples 1-10 in Tables 1 and 2, and Comparative Examples 1 and 2, the storage capacity retention rates of the secondary battery cells in Comparative Examples 1 and 2 are 79.6% and 80.2%, respectively, and the cycle capacity retention rates are 87.3% and 89.8%, respectively. Examples 1-10 are all higher than Comparative Examples 1 and 2. This is because by setting a coating layer to cover at least part of the surface of the positive electrode active material, the direct contact between the positive electrode active material and the electrolyte is reduced, which helps to reduce side reactions between the positive electrode active material and the electrolyte, reduce lithium ion consumption, and improve the storage performance of the lithium-ion secondary battery. By setting a coating layer including graphene and carbon black, on the one hand, graphene and carbon black are conductive, and coating at least part of the surface of the positive electrode active material can improve the conductivity of the positive electrode active material, reduce the internal resistance of the lithium-ion secondary battery, and improve the cycle performance of the lithium-ion secondary battery; on the other hand, during the charging and discharging process of the lithium-ion secondary battery, the positive electrode sheet undergoes volume change. By setting carbon black particles in the coating layer, they contact and overlap with the carbon nanotubes in the positive electrode sheet, forming contact points in the conductive network, so that the carbon black particles and carbon nanotubes can be interconnected and conduct electricity. Furthermore, the bonding strength and cohesive strength of the positive electrode sheets in Examples 1-10 were not reduced compared to Comparative Examples 1 and 2. By coating at least part of the surface of the positive electrode active material with graphene and carbon black, the contact area between carbon black and graphene and the positive electrode active material is increased, thereby improving the conductivity of the positive electrode active material. This reduces the need to increase the conductivity of the positive electrode active material by increasing the amount of conductive agent added, which is beneficial for reducing the amount of conductive agent used in the positive electrode sheet, increasing the mass ratio of the positive electrode active material and the binder, increasing the bonding strength between the binder and the positive electrode active material, and reducing the risk of the positive electrode active material falling off from the current collector. This is beneficial for improving the storage performance and cycle performance of lithium-ion secondary batteries.
[0182] As shown in Examples 1-4 and Comparative Example 1, the bonding force and cohesive force of the positive electrode sheet in the secondary battery cell are increased compared to Comparative Example 1. The DCR decreases from 3620mΩ to 2480mΩ, 2280mΩ, 1930mΩ, and 3381mΩ, respectively. The storage capacity retention rate and cycle capacity retention rate also increase. By setting the mass ratio of graphene to carbon black to meet the above range, it is beneficial to improve the stability of the coating layer, improve the conductivity of the positive electrode active material, reduce the internal resistance of the lithium-ion secondary battery, and improve the storage performance and cycle performance of the lithium-ion secondary battery.
[0183] Combined with Examples 5-6 and Comparative Example 1, the bonding and cohesive forces of the positive electrode in the secondary battery cell are both increased compared to Comparative Example 1. The DCR decreases from 3620 mΩ to 2783 mΩ in Example 5, the storage capacity retention increases from 80.2% to 87% and 88.5%, respectively, and the cycle capacity retention increases from 89.8% to 95.5% and 92.1%, respectively. Graphene has a suitable particle size distribution, which is beneficial to improving the stability of the conductive network in the positive electrode, reducing the internal resistance of the lithium-ion secondary battery, and improving the storage and cycle performance of the lithium-ion secondary battery. In Example 6, the DCR was 3652 mΩ. This may be because as the graphene particle size increases, the sheet diameter of the multilayer graphene is larger, and the conductivity is slightly reduced, resulting in an increase in internal resistance. However, the larger graphene particle size has a better coating effect on the positive electrode active material, which can reduce the contact area between the positive electrode active material and the electrolyte, reduce the consumption of lithium ions, and thus help improve the storage performance and cycle performance of lithium-ion secondary batteries.
[0184] As shown in Examples 1 and 7-8, different carbon nanotubes can be selected according to actual usage requirements.
[0185] As shown in Examples 1 and 9-10, high-pressure homogenization, by forcing the suspension through a small-aperture homogenizing valve under high pressure, generates significant shear and impact forces, resulting in particle dispersion and refinement. This facilitates the placement of carbon black within the graphene interlayer structure. The pressure during high-pressure homogenization meets the requirement of 1500 psi ≤ P ≤ 2500 psi, which promotes uniform particle distribution in the solution, improves dispersion, and reduces the risk of excessive shear pressure damaging the graphene interlayer structure.
[0186] [Testing methods for individual battery cell parameters]
[0187] (1) Test method for coating layer
[0188] Transmission electron microscopy (TEM) was used to analyze and test the positive electrode active material. The coating layer at the grain boundaries was observed, and within this coating layer, multilayered transparent sheet-like graphene structures and carbon black particles were observed. EDS (Electronic Distribution System) elemental plane distribution was used to observe and determine the elemental composition of the coating layer, and ICP (Inductively Coupled Plasma) analysis determined the mass percentage of each element.
[0189] The XRD patterns of the samples (graphene, coating powder) were tested according to the JIS / K0131-1996 testing standard. Based on the XRD patterns, the corresponding diffraction peaks of the target crystal were located. The peak heights of the diffraction peaks were then determined, thereby determining the diffraction peak intensities. Peak height refers to the height of the peak value (vertical axis of the peak value); the higher the peak height, the greater the diffraction peak intensity.
[0190] Figure 6 This is an XRD pattern of an embodiment of this application, provided by... Figure 6 It can be seen that as the carbon black content increases, the disorder increases, and the peak height of diffraction peak A of graphene in the XRD pattern gradually decreases. By placing carbon black in the interlayer of graphene, the carbon black particles play a supporting role in the sheet structure of graphene, expanding the interlayer spacing of graphene, reducing the interlayer stacking phenomenon and particle agglomeration phenomenon of graphene, and improving the dispersion performance of graphene. In the figure, CB-0, CB-4, CB-8, CB-10, and CB-15 represent the mass ratios of graphene and carbon black in the examples as 1:0, 1:4, 1:8, 1:10, and 1:15, respectively.
[0191] (2) Testing the resistance of the positive electrode
[0192] At 25℃, the battery cells are first charged to 4.25V with a constant current of 0.5C, then charged at 4.25V with a constant voltage until the current is ≤0.05mA. After standing for 5 minutes, the cells are discharged to 2.5V at 0.5C. This is one charge-discharge cycle.
[0193] As an example, at 25℃, the resistance of the positive electrode sheet after cold pressing and laser treatment was tested using a Yuaneng Technology electrode resistance meter (BER2500). The specific testing process is as follows: Take the above-mentioned positive electrode sheet (prepared according to the above process or obtained from disassembly from a secondary battery cell), and cut three 3mm*3mm areas from the left, center, and right sides of the positive electrode sheet respectively. Before use, the resistance and pressure were reset. The three cut electrode sheets were placed under the probe for testing. The resistance of each electrode sheet was measured at two different positions, and the average value of the resistance measured at the six different positions was recorded as the resistance value of the positive electrode sheet. The resistance of the electrode sheet can be understood as the value measured at 0% SOC (state of charge).
[0194] (3) Testing of the 60-day storage capacity retention rate of individual battery cells
[0195] The prepared secondary battery cells were left to stand for 5 minutes, then charged at 1 / 3C to 2.8V under constant temperature conditions of 25℃, left to stand for 5 minutes, then charged at 1 / 3C to 4.25V, and then charged at 4.25V under constant voltage until the current ≤0.05mA, left to stand for 5 minutes, and then charged at 1 / 3C to 2.8V. The discharge capacity was recorded as D0. Subsequently, the secondary battery cells were charged at 1 / 3C under constant current to 4.25V, and then charged at 4.25V under constant voltage until the current ≤0.05mA, left to stand for 5 minutes, and then placed in a high and low temperature chamber at 70℃ for 1 hour and stored at 70℃ for 15 days. Under constant temperature conditions of 25℃, the battery is charged at 1 / 3C constant current to 4.25V every 15 days, then charged at 4.25V constant voltage until the current ≤0.05mA, allowed to stand for 5 minutes, and then charged at 1 / 3C to 2.8V. The discharge capacity after 60 days is recorded as D1. The ratio of this discharge capacity to the initial capacity is used to obtain the storage capacity retention rate, which is calculated as: Storage capacity retention rate = D1 / D0 × 100%. The higher the storage capacity retention rate, the better the storage performance of the secondary battery cell.
[0196] (4) Testing of cycle capacity retention of secondary battery cells
[0197] The prepared secondary battery cells were charged at 0.5C to 4.25V under test conditions of 45℃ and 2.8–4.25V. Then, they were charged at a constant voltage of 4.25V until the current ≤0.05mA, allowed to stand for 5 minutes, and then discharged at 0.5C to 2.5V. This constitutes one charge-discharge cycle. The discharge capacity of this cycle is denoted as Cap1. The secondary battery cells were subjected to the above charge-discharge cycle test in the same manner, and the above operation was repeated for 300 cycles. The discharge capacity of the 300th cycle was recorded as Cap300. The capacity retention rate of the secondary battery cell after 300 cycles is C = [Cap300 / Cap1] × 100%. A larger C value indicates smaller capacity loss and better cycle performance of the secondary battery cell.
[0198] (5) Testing the adhesion of the positive electrode sheet
[0199] As an example, referring to standard GB / T2790-1995, the adhesion strength of the positive electrode sheet can be determined using a tensile testing machine, measured according to the manufacturer's instructions. Specifically, measure the positive electrode sheet prepared above along the direction perpendicular to the machine direction (TD), cut a sample with a width of 30mm and a length of 100-160mm, and attach special double-sided adhesive tape to a steel plate. The tape should be 20mm wide and 90-150mm long. After attaching the cut electrode sample to the double-sided adhesive tape, with the test side facing down, roll it three times in the same direction using a pressure roller. Insert a paper strip with a width equal to the electrode sheet and a length of 80-200mm (greater than the electrode sheet length) under the electrode sheet and fix it with crease tape. Use a tensile testing machine to test the adhesion strength of the positive electrode sheet. The greater the bonding force between the positive electrode active material layer and the positive electrode current collector in the positive electrode sheet, the higher the bonding strength between the positive electrode active material and the current collector. Conversely, the lower the bonding strength between the active material and the current collector in the negative electrode active material layer, the lower the bonding strength between the active material and the current collector.
[0200] (6) Testing the cohesive force of the positive electrode sheet
[0201] As an example, measure the positive electrode sheet prepared above along the direction perpendicular to the mechanical direction (TD), and cut a positive electrode sheet sample with a width of 30 mm and a length of 90-150 mm. Attach the cut electrode sheet sample to double-sided adhesive tape, and then attach green tape to the electrode sheet sample. The green tape should be 20 mm wide and 90-150 mm long. The portion of the green tape not in contact with the electrode sheet should be attached to the tape, with the tape and tape in a straight line. Use corrugated adhesive to bond the green tape to the tape joint. Before testing, roll the portion of the green tape in contact with the electrode sheet three times in the same direction with a pressure roller. Insert a paper strip with a width equal to the electrode sheet and a length of 80-200 mm (greater than the electrode sheet length) under the electrode sheet and fix it with corrugated adhesive. Use a tensile testing machine to test the cohesive force of the electrode sheet. The greater the force between active material particles in the positive electrode active material layer, the stronger the interaction force between active materials in the positive electrode sheet; conversely, the smaller the force, the weaker the interaction force between active materials in the electrode sheet.
[0202] (7) Test method for volumetric particle size distribution
[0203] As an example, the volumetric particle size distribution of the coating layer can be determined using a particle size analyzer-laser diffraction method. Specifically, refer to standard GB / T19077-2016, using a laser diffraction scattering particle size analyzer, and perform measurements according to the manufacturer's instructions. For instance, before preparing the positive electrode sheet, take an appropriate amount of sample (graphene, carbon black, and coating powder), and test the average volumetric particle size of the sample using a Malvern 3000 (MasterSizer 3000) laser particle size analyzer. Take an appropriate amount of the sample to be tested (the sample concentration should be 8-12% opacity), add 20 ml of deionized water, and simultaneously overheat for 5 minutes (53 kHz / 120 W) to ensure complete dispersion of the sample. Then, measure the sample according to GB / T19077-2016 / ISO 13320:2009.
[0204] Figure 7 This is a schematic diagram of the volumetric particle size distribution of graphene according to an embodiment of this application. Figure 7 The graphene shown has a Dv50 of 2.03 μm and a Dv90 of 4.74 μm. Figure 8 This is a schematic diagram of the volumetric particle size distribution of the coating powder according to an embodiment of this application, where the mass ratio of graphene to carbon black is 1:8. Figure 8 In the coating powder shown, Dv50 is 0.173 μm and Dv90 is 1.539 μm. By placing carbon black in the interlayer of graphene, the interlayer stacking phenomenon of graphene is reduced, and the Dv50 of the coating powder is smaller.
[0205] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, are also included in the scope of this application without departing from the spirit of this application.
Claims
1. A lithium-ion secondary battery, characterized in that, include: Positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode active material and carbon nanotubes; At least a portion of the surface of the positive electrode active material is provided with a coating layer, the coating layer comprising graphene and carbon black.
2. The lithium-ion secondary battery according to claim 1, characterized in that, The graphene coats at least a portion of the surface of the positive electrode active material, and the carbon black is disposed between the layers of the graphene.
3. The lithium-ion secondary battery according to claim 1 or 2, characterized in that, The mass ratio of the graphene to the carbon black is 1:4 to 1:
15.
4. The lithium-ion secondary battery according to any one of claims 1-3, characterized in that, The volumetric particle size distribution Dv50 of the graphene satisfies: 5μm≤Dv50≤15μm.
5. The lithium-ion secondary battery according to any one of claims 1-4, characterized in that, The carbon nanotubes include at least one of multi-walled carbon nanotubes, few-walled carbon nanotubes, and single-walled carbon nanotubes.
6. The lithium-ion secondary battery according to any one of claims 1-5, characterized in that, Based on the total mass of the positive electrode active material, the amount of carbon nanotubes added, A, satisfies the following condition: 1 wt.% ≤ A ≤ 3 wt.%.
7. The lithium-ion secondary battery according to any one of claims 1-6, characterized in that, The positive electrode active material includes lithium nickel oxide, and the chemical formula of the lithium nickel oxide satisfies: Li 1+a [Ni x Co y Mn z M b O 2-c M includes at least one of Zr, Al, Ti, Sb, Nb, Te, Mg, B, Ca, V, Ta or Sr, 0.2≥a≥-0.2, 1>x≥0.7, 0.3>y>0, 0.3>z>0, 0.3>b≥0, 0.5≥c≥0.
8. A method for preparing a lithium-ion secondary battery, characterized in that, include: Graphene was added to anhydrous ethanol and dispersed to obtain a graphene dispersion. Carbon black is added to the graphene dispersion and dispersed to obtain a carbon black-graphene dispersion. The carbon black-graphene dispersion was spray-dried to prepare a powder. The positive electrode active material and the powder are mixed and ball-milled to obtain an intermediate. The intermediate is subjected to high-temperature calcination to obtain a positive electrode active material with a coating layer. A positive electrode slurry is prepared using the aforementioned positive electrode active material and carbon nanotubes, and the positive electrode slurry is coated on at least one side surface of the positive electrode current collector to obtain a positive electrode sheet. The positive electrode, negative electrode, and separator are assembled into an electrode assembly. The electrode assembly is placed in an outer packaging and sealed. After injecting electrolyte and sealing, a lithium-ion secondary battery is obtained.
9. The preparation method according to claim 8, characterized in that, The dispersion process includes at least one of high-speed shearing, ultrasonic treatment, and high-pressure homogenization.
10. The preparation method according to claim 8 or 9, characterized in that, The pressure for the high-pressure homogenization process is 1500 psi to 2500 psi.
11. The preparation method according to any one of claims 8-10, characterized in that, The mass ratio of the positive electrode active material to the powder satisfies: 100:(1:1.2).
12. An electrical appliance, characterized in that, include: The lithium-ion secondary battery according to any one of claims 1-7; And / or, the lithium-ion secondary battery obtained by the preparation method according to any one of claims 8-11, wherein the lithium-ion secondary battery is used to provide electrical energy to the electrical device.